2015
DOI: 10.3389/fmicb.2015.00964
|View full text |Cite
|
Sign up to set email alerts
|

IncF plasmid diversity in multi-drug resistant Escherichia coli strains from animals in China

Abstract: The purpose of this study was to characterize a collection of 103 multidrug resistance IncF plasmids recovered from Escherichia coli of food producing and companion animals between 2003 and 2012. A total of 103 incF plasmids were characterized using an established PCR-based IncF replicon sequence typing (RST) system to identify FII, FIA, and FIB (FAB) groups. Plasmids were also analyzed using-restriction fragment length polymorphism (RFLP). Antibiotic Resistance determinants blaCTX-M, plasmid-mediated quinolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 52 publications
14
57
0
1
Order By: Relevance
“…The two isolates although not clonally related, shared the same plasmids (Col440I) harbouring AMR genes (qnrB19) due to horizontal gene transfer. Studies have shown that the IncF and IncHI2 plasmids mainly found in E. coli strains, are frequently detected in humans and animals serving as reservoirs for the spread of AMR genes and have been associated with MDR E. coli [43,59]. This evidence supports our study results and explanation of a possibility of horizontal gene transfer of AMR genes harboured in the plasmids.…”
Section: Discussionsupporting
confidence: 91%
“…The two isolates although not clonally related, shared the same plasmids (Col440I) harbouring AMR genes (qnrB19) due to horizontal gene transfer. Studies have shown that the IncF and IncHI2 plasmids mainly found in E. coli strains, are frequently detected in humans and animals serving as reservoirs for the spread of AMR genes and have been associated with MDR E. coli [43,59]. This evidence supports our study results and explanation of a possibility of horizontal gene transfer of AMR genes harboured in the plasmids.…”
Section: Discussionsupporting
confidence: 91%
“…The diversity of plasmid types was increased in comparison with those in previous report (Tamang et al, 2013b), which may reflect more influx of various antimicrobial-resistant genes. Among IncF plasmids in the bla CTX-M-55 -positive E. coli isolates from animals in China, F33 plasmids were the most prevalent replicon STs (Yang et al, 2015). In contrast, F1 types, which are commonly found to carry ESBL genes (Brolund, 2014), were most predominantly identified in this study.…”
Section: Discussionmentioning
confidence: 53%
“…Results from the PlasmidFinder pipeline indicated that the isolated E. coli strains carried an IncF plasmid (replicon type II-IA-IB). The conjugative plasmids of the IncF family range in size from 45 to 200 kb [16, 51,52]. They seem to have a narrow host range specific to the Enterobacteriaceae, being mostly found in E. coli.…”
Section: Overview Of the Draft Genomes Of The Esbl-producing Enterobamentioning
confidence: 99%
“…They seem to have a narrow host range specific to the Enterobacteriaceae, being mostly found in E. coli. Furthermore, they are the predominant plasmids involved in the dissemination of bla CTX-M-15 and are widely reported in bacteria isolated from humans, animals and the environment [52]. IncFII-IA-IB plasmids carrying bla CTX-M have been implicated in community-associated infections on several continents, emphasizing the epidemic nature and global distribution of these plasmids [53,54].…”
Section: Overview Of the Draft Genomes Of The Esbl-producing Enterobamentioning
confidence: 99%